Morpho-Molecular Identification of Plant Pathogen Infecting Bulb Onion (Allium cepa L.) Production Under Protected Cultivation - Jennifer P. Celades; Marilyn M. Belarmino; Catherine C. Arradaza; Robelyn T. Piamonte; Zenaida C. Gonzaga (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study was conducted to identify the fungal pathogen associated with bulb onion production under protected cultivation through combined morphological and molecular identification. Onion leaves showing yellowing, wilting, and purple-to-black lesions were collected from infected plants and subjected to fungal isolation, morphological examination, pathogenicity testing, and molecular analysis. Based on colony and spore characteristics, together with the results of pathogenicity test, the pathogen was identified as Alternaria porri, which is the causal agent of purple blotch disease, fulfilling Koch’s postulates. However, molecular identification based on Internal Transcribed Spacer (ITS) ribosomal DNA sequencing revealed high similarity (98.58– 98.79%) to Nigrospora sphaerica. This difference may be attributed to the faster growth rate and dominance of N. sphaerica in vitro, which likely overshadowed the slower-growing A. porri during DNA amplification and sequencing. Phylogenetic analysis additionally supported the clustering of isolates within the N. sphaerica clade, distinct from A. porri. The contrasting morphological and molecular findings show the occurrence of mixed fungal infections, where A. porri acts as the primary pathogen, and N. sphaerica functions as a secondary colonizer or opportunistic fungus. These results show the limitations of single-method identification and point out the need to integrate morphological, pathogenicity, and molecular approaches for accurate pathogen diagnosis in complex disease systems.